2019
DOI: 10.1007/s40684-019-00059-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Non-torque Loads and Carrier Pinhole Position Errors on Planet Load Sharing of Wind Turbine Gearbox

Abstract: The effects of carrier pinhole position errors and non-torque loads on the load sharing of planet gears in a conventional-type three-point suspension wind turbine gearbox were investigated. A 1/4 scale-down model of a 2-MW class wind turbine gearbox was used, and a parametric study was conducted using a three-dimensional analysis model capable of performing system-level analysis. Axial force, radial force, and bending moment were used as non-torque loads, and the mesh load factor was used as an index represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…As previous studies reported, the power transmitted to each planet gear appeared as a periodic function depending on the carrier rotation angle whether only non-torque load or both non-torque load and carrier pinhole position error were considered. 6,17 Furthermore, because the actual carrier pinhole position error of the PGS was 50 mm presented by the manufacturer, an error of + 100 mm was applied to pinhole 1 to assume the worst load-sharing condition. without any floating member.…”
Section: Load-sharing Characteristics Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…As previous studies reported, the power transmitted to each planet gear appeared as a periodic function depending on the carrier rotation angle whether only non-torque load or both non-torque load and carrier pinhole position error were considered. 6,17 Furthermore, because the actual carrier pinhole position error of the PGS was 50 mm presented by the manufacturer, an error of + 100 mm was applied to pinhole 1 to assume the worst load-sharing condition. without any floating member.…”
Section: Load-sharing Characteristics Analysismentioning
confidence: 99%
“…In practice, however, it is well-known that uneven load sharing occurs owing to non-torque loads and various manufacturing and assembly errors. [1][2][3][4][5][6][7] Because uneven load sharing, due to manufacturing and assembly errors, reduces the life of planet gears, many studies have attempted to solve this problem. Kahraman 4 developed a mathematical model of a PGS to analyze the dynamic load-sharing characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations